The EuroSIDA study: regional differences in the HIV-1 epidemic and treatment response to antiretroviral therapy among HIV-infected patients across Europe--a review of published results - Podlekareva, Daria; Bannister, Wendy; Mocroft, Amanda; Abrosimova, Ludmila; Karpov, Igor; Lundgren, Jens D; Kirk, Ole (Central European Journal of Public Health, 2008)
EuroSIDA is a pan-European observational study that follows 14,265 HIV-infected patients from 31 European countries, Israel and Argentina, of which 2,560 are patients from eastern Europe (EE). The study group has performed several analyses addressing regional differences in the HIV-epidemic across Europe, where all countries were divided into five regions: south, west central, north, east central Europe and EE. Significant regional differences in patients' characteristics and pattern of AIDS diagnoses were documented. More patients from EE were diagnosed with tuberculosis compared to other regions. Significantly fewer HIV-infected patients in EE, who fulfilled the criteria for starting combination antiretroviral therapy (cART), actually received cART as compared with other regions of Europe. Those, receiving cART in EE had a lower initial virologic response rate irrespectively of the regimen used, although it has improved within years. Besides, treatment failure was more common in this region. Thus, improvements in the clinical management of HIV patients in EE are urgently needed. Strategies include creating scientific collaborations for HIV clinicians as well as teaching clinicians about the most advanced HIV management at clinically oriented courses held in eastern Europe.
Keywords: Anti-Retroviral Agents; dospělí; Female; Europe; Adult; výsledek terapie; ženské pohlaví; HIV Infections; HIV-1; lidé; Evropa; Treatment Outcome; antiretrovirové látky; HIV infekce; kohortové studie; Cohort Studies; prospektivní studie; Male; Prospective Studies; lidé středního věku; mužské pohlaví; Middle Aged; Humans